Paleodust variability since the Last Glacial Maximum and implications for iron inputs to the ocean. Issue 8 (28th April 2016) - Albani, S.; Mahowald, N. M.; Murphy, L. N.; Raiswell, R.; Moore, J. K.; Anderson, R. F.; McGee, D.; Bradtmiller, L. I.; Delmonte, B.; Hesse, P. P.; Mayewski, P. A.
Abstract: Changing climate conditions affect dust emissions and the global dust cycle, which in turn affects climate and biogeochemistry. In this study we use observationally constrained model reconstructions of the global dust cycle since the Last Glacial Maximum, combined with different simplified assumptions of atmospheric and sea ice processing of dust‐borne iron, to provide estimates of soluble iron deposition to the oceans. For different climate conditions, we discuss uncertainties in model‐based estimates of atmospheric processing and dust deposition to key oceanic regions, highlighting the large degree of uncertainty of this important variable for ocean biogeochemistry and the global carbon cycle. We also show the role of sea ice acting as a time buffer and processing agent, which results in a delayed and pulse‐like soluble iron release into the ocean during the melting season, with monthly peaks up to 17 Gg/month released into the Southern Oceans during the Last Glacial Maximum (LGM). Key Points: Data‐constrained time‐slice CESM simulations estimate global dust variability since LGM Budgets and uncertainties in dust and soluble iron deposition to key ocean regions for biogeochemical cycles Elevated soluble iron inputs to the Atlantic sector of the Southern Ocean in the LGM